Impact of practice training loads on neuromuscular and perceptual fatigue during an NCAA Division III collegiate football season. - Schimenz, John M. (My University, 2019)
PURPOSE: This study examined neuromuscular fatigue management from a daily undulating practice periodization plan during an NCAA Division III collegiate football season. METHODS: Thirty university football players participated in this study during the first seven weeks of the competition season. Triaxial accelerometers were worn at every practice to track mechanical load. Neuromuscular fatigue was assessed through loaded countermovement jump and perceptual fatigue from wellness variables on Monday, Wednesday, and Friday mornings. One-way analyses of variance with repeated measures determined significant differences between days in all variables, and Cohen’s d determined effect sizes. RESULTS: Significant differences in mechanical load were identified between all days of the practice week. All jump variables had trivial to small improvements from Monday to Friday. Perceptions of fatigue, soreness, and overall well-being showed moderate to large negative effect sizes from Monday to Wednesday; however, these values improved from Wednesday to Friday so that Friday had trivial or small negative effect sizes when compared to Monday. CONCLUSION: Neuromuscular and perceptual fatigue were successfully managed throughout the practice week.
Keywords: Kinesiology; Exercise -- Physiological aspects; Football